Effect of aloe vera as a preprocedural rinse in reducing aerosol contamination during ultrasonic scaling - Benna Paul; Radhamoni Madhavan Pillai Baiju; Nafeesa Beevi Raseena; Periera Shibu Godfrey; Puthenpurayil Ibrahimkutty Shanimole (Wolters Kluwer Medknow Publications, 2020)
Background: The use of preprocedural mouth rinse is one of the recommended ways to reduce aerosol contamination during ultrasonic scaling. Different agents have been tried as preprocedural mouth rinse. Chlorhexidine and povidone-iodine significantly reduce the viable microbial content of aerosol when used as a preprocedural rinse. Studies have shown that aloe vera (AV) mouthwash is equally effective as chlorhexidine in reducing plaque and gingivitis. There is no published literature on the role of AV as a preprocedural mouth rinse. Hence, this study compared the effect of 94.5% AV to 0.2% chlorhexidine gluconate (CHX) and 1% povidone-iodine (PVP-I) as preprocedural mouth rinses in reducing the aerosol contamination by ultrasonic scaling. Materials and Methods: Sixty subjects were divided into three groups based on the preprocedural rinse use (0.2% CHX, 1% PVP-I, and 94.5% AV). Ultrasonic scaling was done for 20 min in the same closed operatory for all the subjects after keeping blood agar plates open at two standardized locations. Colony forming units (CFUs) on blood agar plates were counted, and predominant bacteria were identified after incubation at 37°C for 48 h. Results: There was statistically significant difference in the CFU counts between CHX group and PVP-I group and between AV group and PVP-I group. There was no difference between CHX group and AV group at both the locations. Conclusion: 94.5% AV as a preprocedural rinse is better than 1% PVP-I and comparable to 0.2% CHX in reducing CFU count.